Schienengüterverkehr an der Schnittstelle zum Seeschiff. Integration in der Transportkette. - Schönemann, René (Deutscher Verkehrs-Verl., 2010)
An den Grenzen zwischen zwei logistischen Teilsystemen müssen sowohl Güter- als auch Informationsflüsse Barrieren überwinden. Eine Integration der Teilsysteme zu Transportketten soll helfen, diese abzubauen. Am Beispiel der Schnittstelle zwischen Seeschiff und Schienengüterverkehr ist zu erkennen, welche Schwierigkeiten bei der Integration zweier Systeme auftreten können.

At the interface between two logistic subsystems, goods as well as information have to pass through barriers. By linking the subsystems, a transport chain is created. It has been found out that processes between the intermediaries of the transport chain seaport-rail are not well adjusted. A low level of communication between the intermediaries (ports, freight forwarders, railway transport companies, etc.), leads to conflicts in rail freight transport. Additional time buffers which are planned by railway companies and freight forwarders due to insecurities in transport flow make it slow and untimely. That makes it difficult for the intermediaries to plan own activities in an optimal way. The untimely trains let transhipment processes in ports consume more time than needed since transhipment works are not adjusted to freight train flows. With a better integration of railway processes the transport chain shall be better adjusted and the ship-to-rail transhipment flow becomes smoother.
Ship-to-rail transhipment.
Keywords: Verkehr; Güterverkehr; Transport; Schienengüterverkehr; Wasserverkehr; Seehafen; Seeschiffsverkehr; Containerverkehr; Transportkette; Logistik; Güterumschlag; Seeschifffahrt; Hinterland